Probable Interaction Between Warfarin and Banana Flakes Supplement. (2nd July 2015) - King, Amber E.; Strnad, Kyle
Abstract : Purpose: To describe a case of subtherapeutic international normalized ratio (INR) associated with concomitant use of warfarin and banana flakes in a patient with diarrhea. Summary: A man in his 30s was hospitalized for an elective procedure, but his stay was complicated by cerebral venous thrombosis requiring intravenous infusion of unfractionated heparin, ventilator‐associated pneumonia, bacteremia requiring broad‐spectrum antimicrobials and percutaneous endoscopic gastrostomy tube placement, and diarrhea. Eventually, the heparin was transitioned to warfarin. After several days of therapeutic INR, the INR became subtherapeutic and remained so for 3 days. The decreased INR correlated temporally with initiation of consistent administration of dried banana flakes to treat diarrhea and the subsequent decrease in the rate and extent of diarrhea. Diarrhea decreases the amount and activity of vitamin K–producing intestinal flora and dietary vitamin K absorption, resulting in increased INR. Resolution of diarrhea secondary to banana flakes administration in this patient may have contributed to the decreased INR by causing a relative increase in vitamin K–producing flora and vitamin K absorption. A probability score of 5 was obtained upon applying the Drug Interaction Probability Scale modified to address interactions between warfarin and dietary supplements, indicating a probable interaction between warfarin and banana flakes. Conclusion: Concomitant use of warfarin and banana flakes supplements may result in a reduced rate and extent of diarrhea and may be associated with subtherapeutic INR and decreased warfarin efficacy. Practitioners must be aware of this potential interaction and closely monitor INR and adjust warfarin doses accordingly.